1978
DOI: 10.1007/bf00606680
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of norethindrone in human subjects

Abstract: A competitive protein binding assay for norethindrone was developed to measure plasma levels in human subjects. The plasma levels were considerably higher in women than in men, especially at low dose levels. The plasma levels were directly related to the dose in men; but greater variations in the plasma levels were observed in women. The plasma half-life was about 5 h in both sexes with single oral doses of 5 to 20 mg. A comparative bioavailability study with norethindrone from 2 different manufacturers, formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…A competitive protein binding assay has been described by Okerholm et al (1978). A competitive protein binding assay has been described by Okerholm et al (1978).…”
Section: Norethisterone (Norethindrone)mentioning
confidence: 99%
See 1 more Smart Citation
“…A competitive protein binding assay has been described by Okerholm et al (1978). A competitive protein binding assay has been described by Okerholm et al (1978).…”
Section: Norethisterone (Norethindrone)mentioning
confidence: 99%
“…Okerholm et al (1978) have compared the plasma concentrations of norethisterone after 2 different preparations of the drug. Okerholm et al (1978) have compared the plasma concentrations of norethisterone after 2 different preparations of the drug.…”
Section: Norethisteronementioning
confidence: 99%
“…According to the previous report, 4) the main metabolic pathway of gemfibrozil in humans was the oxidation of the 5῎-methyl group, yielding a hydroxymethyl group, which was further oxidized to a carboxylic acid. Another pathway included the oxidation of the 4῎-C of the aromatic ring to a phenol.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, these phase I metabolites as well as the unchanged gemfibrozil undergo phase II metabolism mostly by glucuronidation, and are excreted into the urine as the major route of elimination. 4) In vitro, we have found that gemfibrozil is oxidized by human liver microsomes at more than one positions producing a mixture of hydroxylated-form metabolites. These metabolites had the same molecular weight of 266 and were positional isomers with regard to the hydroxyl group.…”
Section: )mentioning
confidence: 97%
See 1 more Smart Citation